C4 anatomy can evolve via a single developmental change. (17th December 2018) - Lundgren, Marjorie R.; Dunning, Luke T.; Olofsson, Jill K.; Moreno‐Villena, Jose J.; Bouvier, Jacques W.; Sage, Tammy L.; Khoshravesh, Roxana; Sultmanis, Stefanie; Stata, Matt; Ripley, Brad S.; Vorontsova, Maria S.; Besnard, Guillaume; et al.
Abstract: C4 photosynthesis is a complex trait that boosts productivity in warm environments. Paradoxically, it evolved independently in numerous plant lineages, despite requiring specialised leaf anatomy. The anatomical modifications underlying C4 evolution have previously been evaluated through interspecific comparisons, which capture numerous changes besides those needed for C4 functionality. Here, we quantify the anatomical changes accompanying the transition between non‐C4 and C4 phenotypes by sampling widely across the continuum of leaf anatomical traits in the grass Alloteropsis semialata . Within this species, the only trait that is shared among and specific to C4 individuals is an increase in vein density, driven specifically by minor vein development that yields multiple secondary effects facilitating C4 function. For species with the necessary anatomical preconditions, developmental proliferation of veins can therefore be sufficient to produce a functional C4 leaf anatomy, creating an evolutionary entry point to complex C4 syndromes that can become more specialised.